Rate of Improvement of Pain and Function in Mid-Portion Achilles Tendinopathy with Loading Protocols: A Systematic Review and Longitudinal Meta-Analysis - Murphy, M.; Travers, Merv; Gibson, W.; Chivers, P.; Debenham, J.; Docking, S.; Rio, E. (Adis International Ltd., 2018)
© 2018 Springer International Publishing AG, part of Springer Nature Background: Mid-portion Achilles tendinopathy is prevalent within both the athletic and non-athletic populations and loading protocols for Achilles tendinopathy are effective over time, though the rate of symptom change throughout rehabilitation is unknown. Objective: The objective of this study was to determine the rate of change in pain and function over time in patients while completing a loading protocol for mid-portion Achilles tendinopathy. Methods: A systematic review and longitudinal meta-analysis was conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The databases PubMed, CINAHL (Ovid) and CINAHL (EBSCO) were searched for articles published from inception until 31 July, 2017. Our search focused on clinical trials and cohort studies examining changes in pain and function when completing a loading protocol for mid-portion Achilles tendinopathy. The primary outcome measure assessing pain and function was the Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire. Results: A total of 31 separate cohorts (24 studies) were eligible, with follow-up ranging from 2 weeks to 6 months. The data were pooled to create the mean (standard deviation) of change from baseline at each time point. The data demonstrated an improvement in pain and function as early as 2 weeks that appeared to peak at 12 weeks with a mean (standard deviation) of 21.11 (6.61) points of change on the VISA-A. Conclusion: The improvement in pain and function during rehabilitation suggests future research should be directed toward investigating contributing mechanisms as tendon structure on imaging does not change within 2 weeks and muscular hypertrophy is not seen for at least 4 weeks following the inception of a loading protocol. Systematic Review Registry: PROSPERO registration number: CRD42017062737 (https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=62737)